DER BEGRIFF „SPARSAMKEIT“ IN DEN SPRICHWÖRTERN UNTER DEM ASPEKT DER KULTURWISSENSCHAFTLICHEN LINGUISTIK (BASIEREND AUF RUSSISCH, LETTISCH, DEUTSCH UND ENGLISCH) - Bredis, Mikhail (Proverbium - Yearbook, 2014)
This article provides a comparison between Russian, Latvian, German and English proverbs, related to the topic of frugality in relation to money and wealth. When considering the Latvian proverbs, Latgalian proverbs also were considered, because the Latgalian written language is regarded as a historical subspecies of Latvian. Particular attention is paid to the specifics and differences of the proverbs in languages under examination. Proverbs are considered with reference to different monetary units. In this article the proverb meaning similarity of all analyzed languages is noted in many cases, at the same time there is a significant var-iation of the used images.